Kinerja Lembaga Keuangan Bank Syariah Di Indonesia - Dian Indah Cahyani (ITB AAS INDONESIA, 2015)
The purpose of this study is to see the performance of financial institutions, especially sharia banking in Indonesia in the period 1998 to mid 2015 in terms of market share when compared with conventional banking. The research method using the literacy method by looking at the data that support the research problems undertaken. The results show that for 14 years from 1998 to 2012, the level of development of Islamic banks in Indonesia is very remarkable, with an average growth of around 45% -78% per year, but in 2013 to mid 2015 results was found not as expected, where the market share of sharia banks is only 4.85% compared to conventional banks.